2006
DOI: 10.1248/cpb.54.1545
|View full text |Cite
|
Sign up to set email alerts
|

Structures of New Cucurbitane-Type Triterpenes and Glycosides, Karavilagenins and Karavilosides, from the Dried Fruit of Momordica charantia L. in Sri Lanka

Abstract: The Cucurbitaceae plant Momordica (M.) charantia L. is cultivated in Asian countries and the fruit of this plant has been used as a bitter stomachic, a laxative, an antidiabetic, and an anthelmintic for children in Chinese, Indian Ayurvedic, and Indonesian Jamu traditional medicines. The alcoholic extract from the fruit of M. charantia originated in Sri Lanka was reported to inhibit the increase in serum glucose levels after glucose-loaded rats.1) In addition, Several cucurbitane-type triterpene glycosides wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 27 publications
2
64
0
1
Order By: Relevance
“…The combined EtOAc soluble layer was subjected to repeated silica gel column chromatography and further purification by semi-preparative HPLC to yield compounds 1-9. The eight known compounds (2)(3)(4)(5)(6)(7)(8)(9) were identified by comparing their physical and spectral data with the reported values. The structure of the new sterol (1) was elucidated as follows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined EtOAc soluble layer was subjected to repeated silica gel column chromatography and further purification by semi-preparative HPLC to yield compounds 1-9. The eight known compounds (2)(3)(4)(5)(6)(7)(8)(9) were identified by comparing their physical and spectral data with the reported values. The structure of the new sterol (1) was elucidated as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Previous pharmacological studies have showed that the extracts or compounds of tissues of M. charantia possess anti-diabetic and anti-inflammatory activities. [1][2][3] Chemical investigations of M. charantia also revealed that more than seventy cucurbitane-type triterpenes have been isolated form the fruits, [3][4][5][6][7][8][9][10][11][12] seeds, 13,14 root, 15 and leaves and vines 16,17 of M. charantia. As part of our program aimed at the discovery of bioactive secondary metabolites from Taiwanese M. charantia, we had reported the isolation and structure elucidation of twenty-five cucurbitane-type triterpenoids from the MeOH extract of the stems of this plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cucurbitane-type triterpenoids and their aglycones have shown some biological effects beneficial in treating diabetes and obesity, and possess anticancer, anti-HIV and antifeedant properties [7,39]. More than fifty cucurbitacins and cucurbitane glycosides from the fruits, seeds, leaves, vines and stems have been reported [40][41][42][43][44][45][46][47][48]. Recently, Chen et al (2008) isolated and structured elucidation of nineteen cucurbitacins named kuguacins A-E from the roots of MC [49] and kuguacins F-S [50] from the vines and leaves of MC.…”
Section: Phytochemicals and Cucurbitane Triterpenoidsmentioning
confidence: 99%
“…Tissues of this plant have extensively been used as folk medicine for the treatment of diabetes and diseases of liver in Taiwan. The previous pharmacological studies have demonstrated that the extracts or constituents of tissues of M. charantia possess anti-diabetic and anti-inflammatory activities.1-3) The Cucurbitaceae plants have been recognized as rich sources of cucurbitane-type triterpenoids possessing anti-diabetic activity.3) More than seventy cucurbitane-type triterpenoids have been identified from the fruits, [3][4][5][6][7][8][9][10] seeds, 11,12) roots, 13) leaves and vines 14,15) of M. charantia. As part of our program aimed at the discovery of the cucurbitane-type triterpenes from M. charantia originated in Taiwan, we have reported the isolation and structure elucidation of 21 cucurbitane-type triterpenoids from the MeOH extract of the stems of this plant.…”
mentioning
confidence: 99%